Program SMART (Smart Eating And Living For Teens) sebagai Upaya Edukasi Interaktif Peningkatan Kualitas Kesehatan Remaja - Ita Puji Lestari; Ariesti, Niken Dyah; Yuswantina, Richa (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
The current lifestyle of adolescents shows a tendency towards unhealthy consumption patterns, especially the high consumption of fast food, foods high in sugar, and sugary drinks. This phenomenon also occurs at SMA Negeri 2 Ungaran, where easy access to unhealthy foods affects students' eating habits. This kind of consumption pattern risks increasing the prevalence of obesity, type 2 diabetes mellitus, and other metabolic diseases from a young age. Through nutrition education activities conducted to students in grades X and XI, interactive approaches such as visual simulation of sugar levels, understanding nutrition labels, and inspirational stories were used to increase students' awareness of the importance of healthy eating. The results of the activity showed a significant increase in student knowledge, as evidenced by the increase in pre-test scores from 56 to 85 in the post-test. In addition, most of the students expressed their commitment to reduce their consumption of unhealthy food and drinks and start bringing healthy lunches from home. This activity also highlighted the importance of education on food-drug interactions, which are often overlooked but can interfere with therapeutic effectiveness and nutritional status. With a good understanding of nutrition, adolescents are expected to become agents of change who not only take care of their own health, but also contribute to spreading health information in the surrounding environment. Continuous education and participatory approaches are key in building nutrition literacy and healthy consumption behavior among adolescents.   ABSTRAK Gaya hidup remaja saat ini menunjukkan kecenderungan pola konsumsi yang tidak sehat, khususnya tingginya konsumsi makanan cepat saji, makanan tinggi gula, dan minuman manis. Fenomena ini juga terjadi di SMA Negeri 2 Ungaran, di mana akses mudah terhadap makanan tidak sehat memengaruhi kebiasaan makan siswa. Pola konsumsi semacam ini berisiko meningkatkan prevalensi obesitas, diabetes melitus tipe 2, dan penyakit metabolik lainnya sejak usia muda. Melalui kegiatan edukasi gizi yang dilakukan kepada siswa kelas X dan XI, pendekatan interaktif seperti simulasi visual kadar gula, pemahaman label gizi, dan cerita inspiratif digunakan untuk meningkatkan kesadaran siswa terhadap pentingnya pola makan sehat. Hasil kegiatan menunjukkan peningkatan pengetahuan siswa yang signifikan, dibuktikan dengan kenaikan skor pre-test dari 56 menjadi 85 pada post-test. Selain itu, sebagian besar siswa menyatakan komitmen untuk mengurangi konsumsi makanan dan minuman tidak sehat serta mulai membawa bekal sehat dari rumah. Kegiatan ini juga menyoroti pentingnya edukasi mengenai interaksi antara makanan dan obat yang sering kali diabaikan, namun berisiko mengganggu efektivitas terapi dan status gizi. Dengan pemahaman gizi yang baik, remaja diharapkan mampu menjadi agen perubahan yang tidak hanya menjaga kesehatannya sendiri, tetapi juga berkontribusi dalam menyebarkan informasi kesehatan di lingkungan sekitarnya. Edukasi yang berkelanjutan dan pendekatan partisipatif menjadi kunci dalam membangun literasi gizi dan perilaku konsumsi sehat di kalangan remaja.